The sustainability of school improvement in challenging contexts : case study of public schools in Antofagasta, Chile - Espinoza Zamorategui, Karla (2014)
This master thesis examines the factors that determine the sustainability of improvement made by schools in challenging contexts. The study focuses on nine public schools in Antofagasta, Chile. These schools have undertaken an improvement program during a given time span. As a result, the schools have achieved different outcomes despite having similar internal and external situations. Thus, the study will help us to understand in what ways the schools have improved and what is needed to assure the sustainability of their improvement achieved.